Periodistas víctimas de la delincuencia durante las coberturas en Ecuador - Zambrano Chonillo, Romina Paola (2023)
Journalists work under pressure, having to deliver material on the facts urgently, without the possibility of carefully processing what is happening and without considering the psychological impact left by coverage in critical situations: a bulletproof vest is useless in such coverage. and security protocols do not tell you what to do or how to prevent those circumstances of emotional risk. The present investigation was born with a purpose and it is to demonstrate the lack of security to the hundreds of professionals who operate and work in different cities of Ecuador. Since the social or economic problems of a particular region lead to a repressive society that seeks to express its discontent, violent acts against journalists are happening all over the world. Based on protests and where communicators are most at risk. As a result, this is a topic that interests many researchers, so understanding the background to this research is crucial to supporting its advancement.